![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ( 2x - 3 ) - ( x - 5 ) = ( x + 7 ) - ( x + 2 )
<=> 2x - 3 - x + 5 = x + 7 - x - 2
<=> x = 3
b)(7x-5)-(6x+4)=(2x+3)-(2x+1)
<=> 7x - 5 - 6x - 4 = 2x + 3 - 2x - 1
<=> x = 11
c)(9x-3)-(8x+5)=(3x+2)
<=> 9x - 3 - 8x - 5 = 3x + 2
<=> -2x = 10
<=> x = -5
d)(x+7)-(2x+3)=(3x+5)-(2x+4)
<=> x + 7 - 2x - 3 = 3x + 5 - 2x - 4
<=> -2x = -3
<=> x = 3/2
ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠᅠ ᅠ
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\frac{3}{4}-\frac{3}{4}:x=\frac{1}{2}\)
\(\frac{3}{4}:x=\frac{3}{4}-\frac{1}{2}\)
\(\frac{3}{4}:x=\frac{1}{4}\)
\(x=\frac{3}{4}:\frac{1}{4}\)
\(x=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{3}{4}-\frac{3}{4}:x=\frac{1}{2}\)
\(\Leftrightarrow\frac{3}{4}:x=\frac{1}{4}\Leftrightarrow x=3\)
b) \(-12.\left(x-5\right)+7.\left(3-x\right)=5\)
\(\Leftrightarrow-12x+60+21-7x=5\Leftrightarrow-19x+81=5\Leftrightarrow-19x=-76\)
\(\Leftrightarrow x=4\)
c) \(\left|7x+3\right|=66\Leftrightarrow7x+3=66\text{ hoặc }-7x-3=66\)
\(\Leftrightarrow7x=63\text{ hoặc }-7x=69\)
\(\Leftrightarrow x=9\text{ hoặc }x=-\frac{69}{7}\)
d) \(\left(x-7\right).\left(x+3\right)< 0\Leftrightarrow x-7< 0\text{ và }x+3>0\Leftrightarrow x< 7\text{ và }x>-3\)
\(\Leftrightarrow-3< x< 7\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3/4-3/4:x=1/2
=>3/4:x=3/4-1/2
=>3/4:x=3/4-2/4
=>3/4:x=1/4
=>x=3/4:1/4
=>x=3/4.4/1
=>x=4
b)-12.(x-5)+7.(3-x)=5
=>-12x+60+21-7x=5
=>81-19x=5
=>19x=81-5
=>19x=76
=>x=76:19
=>x=4
c) |7x+3|=66
=>7x+3=-66 hoặc 7x+3=66
+)Nếu 7x+3=-66
=>7x=-66-3=-66+(-3)=-69
=>x=(-69):7=\(\frac{-69}{7}\)
+)Nếu 7x+3=66
=>7x=66-3=63
=>x=x=63:7=9
d)(x-7)(x+3)<0
=>x-7<0 hoặc x+3<0
+)/nếu x-7<0
=>x<7
+)nếu x+3<0
=>x<-3
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
2|x-6|+7x-2=|x-6|+7x
2|x-6| - |x-6|=7x-(7x-2)
|x-6| = 2
=>x-6 = +2
*x-6=2 *x-6 = -2
x =2+6 x = (-2)+6
x =8 x = 4
2.
|x-5|-7(x+4)=5-7x
|x-5|-7x-28 =5-7x
|x-5|-28 =5-7x+7x
|x-5|-28 = 5
|x-5| = 5+28
|x-5| = 33
=>x-5 = +33
*x-5=33 *x-5=-33
x =38 x = -28
3.
3|x+4|-2(x-1)=7-2x
3|x+4|-2x+2 =7-2x
3|x+4|-2 =7-2x+2x
3|x+4|-2 =7
3|x+4| =7+2
3|x+4| = 9
|x+4| =9:3
|x+4| = 3
=>x+4 = +3
*x+4=3 *x+4=-3
x =-1 x = -7
(x - 5) - 7(x + 4) = 5 - 7x
=> x - 5 - 7x - 28 = 5 - 7x
=> -6x - 33 = 5 - 7x
=> -6x + 7x = 5 + 33
=> x = 38
\(\left(x-5\right)-7\left(x+4\right)=5-7x\)
\(\Leftrightarrow x-5-7x-28=5-7x\)
\(\Leftrightarrow-6x-33=5-7x\)
\(\Leftrightarrow-6x+7x=33+5\)\(\Leftrightarrow x=38\)